2011
DOI: 10.3233/cbm-2011-0224
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in cytochrome P450 1A2 and their interaction with risk factors in determining risk of squamous cell lung carcinoma in men

Abstract: The present case-control study was carried out to investigate the association of functionally important polymorphisms of cytochrome P450 1A2 (CYP1A2) involved in the metabolic activation of tobacco derived procarcinogens with squamous cell carcinoma (SCC) of lung in North Indian men. The study consisted of 200 male cases with SCC of lung and an equal number of age and sex matched healthy controls. Our data showed that variant genotype of CYP1A2*1D and CYP1A2*1F were significantly associated with increased susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Both GSTM1 and GSTT1 gene exhibit an inherited homozygous deletion polymorphism (null genotype), which has been associated with the loss of enzymatic activity and increased vulnerability to cytogenetic damage (Norppa, 2004). As a result of decreased efficiency in protection against carcinogens, the individuals with homozygous deletion polymorphism are considered to be at an increased risk for malignancies (Hayes et al, 2005;Mcllwain et al, 2006;Singh et al, 2010;Ihsan et al, 2011). Many studies have been published on the association of CYP1A1 and GSTM1 polymorphisms and lung cancer susceptibility with inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both GSTM1 and GSTT1 gene exhibit an inherited homozygous deletion polymorphism (null genotype), which has been associated with the loss of enzymatic activity and increased vulnerability to cytogenetic damage (Norppa, 2004). As a result of decreased efficiency in protection against carcinogens, the individuals with homozygous deletion polymorphism are considered to be at an increased risk for malignancies (Hayes et al, 2005;Mcllwain et al, 2006;Singh et al, 2010;Ihsan et al, 2011). Many studies have been published on the association of CYP1A1 and GSTM1 polymorphisms and lung cancer susceptibility with inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been published on the association of CYP1A1 and GSTM1 polymorphisms and lung cancer susceptibility with inconsistent findings. Some of the studies showed the relationship between the polymorphisms of GSTM1 and CYP1A1 Ile/Val genotype (Singh et al, 2010;Ihsan et al, 2011) but other results are contradictory (Le Marchand et al, 1998;London et al, 2000). However, some data of Chinese Han population (Shi et al, 2008) and little data on Mongolian population are still available.…”
Section: Discussionmentioning
confidence: 99%
“…After deleted duplicate and non-relevant studies, finally seven casecontrol studies (Gemignani et al, 2007;Osawa et al, 2007;Zienolddiny et al, 2008;Aldrich et al, 2009;B'Chir et al, 2009;Singh et al, 2010;Gervasini et al, 2013) and one nested case-control study (Pavanello et al, 2012) involving 1675 lung cancer patients and 2393 controls were included.…”
Section: Study Section and Characteristicsmentioning
confidence: 99%
“…Besides, many studies aim at exploring the gene-gene interaction among metabolic enzyme genes (Singh et al, 2011;Ying et al, 2013;Gao et al, 2014), but interaction between CYP2E1 and NAT2 polymorphism has not been reported.…”
Section: Introductionmentioning
confidence: 99%